HUBUNGAN KADAR THYROID STIMULATING HORMONE (TSH) DENGAN FREE THYROXINE (FT4) PADA PASIEN HIPERTIROID - Diah Hastuti; Putu Ayu Parwati; Ni Luh Gede Puspita Yanti (TENTIRO: Jurnal Pendidikan dan Kesehatan, 2026)
Hyperthyroidism is a medical condition characterized by excessive production of thyroid hormones by the thyroid gland. Laboratory tests are an important step in diagnosing hyperthyroidism. The most important and most specific are TSH and FT4 level tests. This study aims to determine the relationship between TSH and FT4 level test results in hyperthyroid patients who underwent examination at Wangaya Regional Hospital, Denpasar City. The type of research used is a correlational research design. The sample in this study was all data from hyperthyroid patients who underwent FT4 and TSH examinations from August to September 2025 at Wangaya Regional Hospital, a total of 40 patients. The results showed that the dominant TSH test results were low, namely 19 people (47.5%) and normal FT4 results were 39 people (97.5%). The results of data analysis using the Spearman test showed a p-value of 0.320, which means p-value>0.05. This indicates no correlation between TSH and FT4 levels in hyperthyroid patients at Wangaya Regional Hospital, Denpasar City. This is likely due to the rapid onset of medication that suppresses FT4, while TSH takes much longer to return to normal.